2015
DOI: 10.1186/s12889-015-1676-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between psychological distress and the most concerning present personal problems among working-age men in Japan

Abstract: BackgroundPersonal problems are known to influence mental health among workers. The current study investigated the most concerning present personal problems which have the greatest impact on psychological distress among working-age Japanese men, rather than issues relating to work tasks or duties.MethodsWe obtained data from the 2010 Comprehensive Survey of Living Conditions conducted by the Ministry of Health, Labour and Welfare. The original survey interviewed 289,363 households in 5,150 randomly selected mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…That the highest odds of distress were found for those with the lowest household income level is consistent with previous findings that financial difficulty increases psychological distress 14,24 . Correspondingly, a study showed that loss of employment is linked to increased distress (study was done in Norway among general population) 13 , as it may lead to financial strain 16,25 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That the highest odds of distress were found for those with the lowest household income level is consistent with previous findings that financial difficulty increases psychological distress 14,24 . Correspondingly, a study showed that loss of employment is linked to increased distress (study was done in Norway among general population) 13 , as it may lead to financial strain 16,25 .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the previous studies on educational differences in mental health problems, low education may be more consistently associated with severe mental health problems than minor psychiatric morbidity 23,[27][28][29][30] , and it correspond with findings from current studies. Positive associations between being unmarried, bereaved, or divorced and psychological distress have been reported in previous studies, but there have been no such associations reported with psychological stress 16,24,25 . As shown in longitudinal studies including a study done for working-age population in Finland 7,14 , there was significant association between living alone and psychological distress in the current study.…”
Section: Discussionmentioning
confidence: 80%
“…Second, as we used an online questionnaire, the sample may have been biased toward individuals who owned a computer and were more familiar with internet use. Third, the current study utilized self-reporting measures, which may exhibit an inherent degree of recall error and bias (particularly regarding class attendance), although this methodology is by no means uncommon in psychological research (68) , (69) .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of original research articles based on secondary data of these surveys have been published in peer-review journals in epidemiology and public health, especially since the 2000s. For example, around 50 journal articles have used secondary data from one of the two major national household surveys on health in Japan: the Comprehensive Survey of Living Conditions 15 34 and the National Nutrition Survey (renamed the National Health and Nutrition Survey in 2003). 17 19 , 25 , 32 , 35 63 Topics covered by the articles using the Comprehensive Survey of Living Conditions include socioeconomic factors, 15 , 20 , 23 , 24 , 27 , 32 inequality, 19 , 21 , 26 , 28 gender differences, 16 , 33 self-rated health, 15 , 24 , 29 mental health, 20 , 27 , 34 activities of daily living, 33 and health-related quality of life.…”
Section: Secondary Data Analysis Of National Health Surveys In Japanmentioning
confidence: 99%
“…For example, around 50 journal articles have used secondary data from one of the two major national household surveys on health in Japan: the Comprehensive Survey of Living Conditions 15 34 and the National Nutrition Survey (renamed the National Health and Nutrition Survey in 2003). 17 19 , 25 , 32 , 35 63 Topics covered by the articles using the Comprehensive Survey of Living Conditions include socioeconomic factors, 15 , 20 , 23 , 24 , 27 , 32 inequality, 19 , 21 , 26 , 28 gender differences, 16 , 33 self-rated health, 15 , 24 , 29 mental health, 20 , 27 , 34 activities of daily living, 33 and health-related quality of life. 16 , 22 Articles using the National (Health and) Nutrition Survey have examined anemia, 41 , 50 oral health, 45 47 , 49 dyslipidemia, 52 , 55 hypertension, 37 , 60 diabetes, 62 weight status and obesity, 35 , 40 , 42 44 and lifestyle-related factors, including tobacco smoking, 45 47 dietary intake, 38 , 39 , 53 , 54 , 58 , 59 , 63 and physical activity.…”
Section: Secondary Data Analysis Of National Health Surveys In Japanmentioning
confidence: 99%